Elderly in process of rehabilitation: nursing care to bodies limited functional (Research, Society and Development, 2021)
Study objective: To analyze the aspects involving care and its implications in the family dynamics of elderly patients with physical disabilities in the process of rehabilitation. Methodology: Study of an interpretative, reflective descriptive and qualitative approach, based on the Theory of Social Relations (TRS) by Moscovici and the Discourse of the Collective Subject (DSC) by Lefèvre and Lefèvre, for its support. It took place in a Specialized Center in Rehabilitation (CER), in the south of Santa Catarina (SC), chosen according to the intention of the research. During the data collection phase, the following techniques were used: systematic observation, hybrid interview, genogram; ecomap. Results: The universe of participants was 08 elderly, being 62.5% (n = 05) men, with a mean age of ±74.2 years; 62.5% (n = 05) residents of Criciúma and 75% (n = 06) in rehabilitation after a cerebrovascular accident (CVA), mean between injury and admission of ±74.3 days and length of stay in the rehabilitation of ±207.2 days. Significant changes were evidenced in the family dynamics of the elderly, who reported receiving genuine and spontaneous care, but the feeling of responsibility for significant changes in the routines of their family members' lives predominates among the participants. Final considerations: Care is something inherent and constitutive of the human being, going beyond Newtonian-Cartesian practices and it is up to the Nurse to help this elderly person in the rehabilitation process and their family/caregiver to understand this complexity, providing subsidies for the elderly binomial -family/caregiver find ways to address the needs now presented to everyone.